2010
DOI: 10.1111/j.1365-3059.2010.02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the root‐knot nematode Meloidogyne enterolobii and development of a SCAR marker for this guava‐damaging species

Abstract: The objectives of this work were to evaluate the genetic variability of Meloidogyne enterolobii by molecular markers, and develop species-specific molecular markers for application in detection. Sixteen M. enterolobii isolates from different geographical regions (Brazil and other countries) and hosts were used in this study. The identification and purification of the populations were carried out based on isoenzyme phenotype. The DNA amplification of the intergenic region (IGS) of the rDNA and of the region bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
60
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 21 publications
4
60
0
8
Order By: Relevance
“…For instance, M. chitwoodi, a meiotic parthenogenetic nematode, has a wide host range and has shown to have significant intraspecific variability and genetic structure between four populations from the USA [4]. In addition, several obligatory mitotic parthenogenetic nematodes having a larger host range were studied (e.g., M. enterolobii), and were characterized by a genetically homogeneous organization [5]. More exhaustive data then need to be generated to explore the potential contribution of each reproductive mode in the genetic structure organization and intraspecific variability.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, M. chitwoodi, a meiotic parthenogenetic nematode, has a wide host range and has shown to have significant intraspecific variability and genetic structure between four populations from the USA [4]. In addition, several obligatory mitotic parthenogenetic nematodes having a larger host range were studied (e.g., M. enterolobii), and were characterized by a genetically homogeneous organization [5]. More exhaustive data then need to be generated to explore the potential contribution of each reproductive mode in the genetic structure organization and intraspecific variability.…”
Section: Introductionmentioning
confidence: 99%
“…), na China. Após alguns estudos (TIGANO et al, 2010;XU et al, 2004) foi verificado que M. enterolobii e M. mayaguensis (RAMMAH; HIRSCHMANN, 1988) que haviam sido relatadas em raízes de Solanum melongena, tratava-se da mesma espécie, resultando numa sinonímia entre esses dois nematoides. A alta taxa de reprodução e a ampla gama de hospedeiros evidencia a agressividade da espécie, capaz de superar fontes de resistência a outras meloidoginoses como M. incognita, M.…”
Section: Introductionunclassified
“…However, Tigano et al (2010) observed similar homogeneity displayed by M. enterolobii populations from different geographic regions in Brazil, thus, it is likely that the lack of variation within the South Phylogenetic analysis using ML for the IGS sequences of these samples showed that the South African M. enterolobii populations and those from GenBank formed an independent cluster with a high bootstrap support value of 90% (Fig.1). This cluster, containing our populations and M. enterolobii from GenBank, was distinct from others and was sandwiched between tropical species and that of cold/temperate adapted Meloidogyne species clusters.…”
mentioning
confidence: 67%
“…In South Africa, it was first reported in Mpumalanga, in 1997 where it led to the decline and eventual death of infected but untreated guava trees (Willers, 1997). This nematode species has also been identified in various parts of the world, such as France, the USA (Florida), two greenhouses in Switzerland, Brazil and China (Blok et al, 2002;Brito et al, 2004;Kiewnick et al, 2009;Tigano et al, 2010;Hu et al, 2011).…”
mentioning
confidence: 97%